Propuesta de un plan estratégico para la empresa Cablevision Gonzanama de la ciudad de Gonzanama - Acaro Vega, Henry Rodrigo (2016)
Strategic planning is the process formalized long-term planning , which is used to define and achieve the goals of the organization, identify the policies and programs necessary to achieve the specific objectives that lead to the goals and establishing methods needed to ensure that they implement policies and strategic plans. To achieve the objectives it is necessary that every company makes use of strategic planning; Thus for the company under study it was determined to perform a "PROPOSAL FOR A STRATEGIC PLAN FOR THE COMPANY Cablevision Gonzanama CITY Gonzanama", as it will significantly improve service and achieved position the company in the market Gonzanama city. For the development of this research work methods such as the historical method, deductive method, inductive method, statistical method, analytical method, descriptive method, and techniques like the interview which was addressed to the manager of the company and surveys of used internal customers in a number of 5 employees and external customers in a number of 204 surveys. The study conducted internal analysis resulting in the EFI matrix a weighted score of 2.76 and showed that there are strengths that are exposed to within the company and external analysis that analyze the economic, political, social factors, Technological determined , Productive and Environmental demonstrated in the EFE Matrix a weighted rating of 3.00, and there are more opportunities than threats for the company. With these results a SWOT analysis of the company was conducted, in which the internal factors such as the strengths and weaknesses and external factors are the opportunities and threats were identified, then the matrix of criteria for high impact is made to give as results FO, FA, DO, DA and assessment with their respective percentages combination. Finally they came to develop the strategic objectives with a total budget of $ 3,670.00 to be taken into consideration by the manager of the company to carry out the strategic plan presented. With the above was reached conclusions and recommendations of which the most important situations obtained during application of the analysis of the entire research work, in order that the manager take the necessary corrective measures for their entity described.